(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article describes the main sources of borrowing the medical terminology in modern English. The authors determine the basic lexical composition of the English medical terminology and describe the process of the formation of medical vocabulary and the main sources of borrowing. The main languages from which the borrowing took place and the ways of borrowing terms are indicated.